Natalizumab (Tysabri) in multiple sclerosis patients - Sacchi, Viola (Farmeconomia. Health Economics and Therapeutic Pathways, 2008)
Multiple sclerosis (MS) is an autoimmune disease where dysregulated immune system elements (i.e. leucocytes) react against different components of the central nervous system (CNS), in particular myelin structures, causing several physical and mental symptoms,often progressing to total disability. While some treatments for MS provide only symptom relief, the most commonly drugs administered for altering the course of the disease are DMTs (disease-modifying therapies); nevertheless for more than ten years the only DMTs available were interferon β, glatiramer acetate (two immunomodulating drugs) and mitoxantrone (an immunosuppressant).